Pattern of Maxillofacial Fractures in South Asian Countries: A Narrative Review Running title: Maxillofacial fractures pattern in south Asian countries. - Rahman, A F M Shakilur; Ahamed, Shaheen; Hakim, Md Abdul (Update Dental College Journal, 2026)
Patterns of maxillofacial fractures vary by region, and they represent a general public health challenge, particularly in South Asia. This literature study examines data from South Asian nations, including Bangladesh, India, Pakistan, and Nepal, to comprehend the demographic trends, fracture sites, causes, and treatment procedures. The largest risk category for traffic accidents is men, primarily in the 20-30 age range. The frequent involvement of motorized two-wheelers highlights the need for increased helmet use and road safety. The most common site for fracture is the mandible, followed by the zygomaticomaxillary complex (ZMC) and maxilla. Treatment options might vary from conservative to open reduction and internal fixation, depending on the severity of the injury and the availability of resources. Data from underrepresented regions such as Sri Lanka, Bhutan, and the Maldives is still inadequate. The results of various treatment approaches, longitudinal trends, and gender differences would all be examined in future research to provide effective management and prevention methods. Update Dent. Coll. j: 2025; 15(2): 32-38